Current-mode leapfrog ladder filters using CDBAs - Tangsrirat, Worapong; Fujii, Nobuo; Surakampontorn, Wanlop (My University, 2002)
In this paper, a possible realization of a current differencing buffered amplifier (CDBA) in the low-voltage operation is proposed. A leapfrog simulation of the current-mode ladder network using the CDBA as active circuit building blocks is then introduced. In order to demonstrate that the CDBA considerably simplifies the leapfrog structure of the current-mode ladder filters, a fifth-order Butterworth low-pass filter and a sixth-order Chebyshev bandpass filter which require a minimum of active components will be presented. PSPICE simulation results are employed to verify the correctness of the realization procedure.